Regional epigenetic differentiation of the Z Chromosome between sexes in a female heterogametic system - Sun, Dan; Maney, Donna L.; Layman, Thomas S.; Chatterjee, Paramita; Yi, Soojin V. (Genome Research, 2019)
In male heterogametic systems, the X Chromosome is epigenetically differentiated between males and females, to facilitate dosage compensation. For example, the X Chromosome in female mammals is largely inactivated. Relative to well-studied male heterogametic systems, the extent of epigenetic differentiation between male and female Z Chromosomes in female heterogametic species, which often lack complete dosage compensation, is poorly understood. Here, we examined the chromosomal DNA methylation landscapes of male and female Z Chromosomes in two distantly related avian species, namely chicken and white-throated sparrow. We show that, in contrast to the pattern in mammals, male and female Z Chromosomes in these species exhibit highly similar patterns of DNA methylation, which is consistent with weak or absent dosage compensation. We further demonstrate that the epigenetic differences between male and female chicken Z Chromosomes are localized to a few regions, including a previously identified male hypermethylated region 1 (MHM1; CGNC: 80601). We discovered a novel region with elevated male-to-female methylation ratios on the chicken Z Chromosome (male hypermethylated region 2 [MHM2]; CGNC: 80602). The MHM1 and MHM2, despite little sequence similarity between them, bear similar molecular features that are likely associated with their functions. We present evidence consistent with female hypomethylation of MHMs and up-regulation of nearby genes. Therefore, despite little methylation differentiation between sexes, extremely localized DNA methylation differences between male and female chicken Z Chromosomes have evolved and affect expression of nearby regions. Our findings offer new insights into epigenetic regulation of gene expression between sexes in female heterogametic systems.
10.1101/gr.248641.119